Reimagining Resistance: Expressions of Palestine Solidarity in Cairo's Underground Heterotopias - Maatouk,Stefan (2025)
This thesis explores how Cairo’s underground music scene navigates the relationship between artistic expression and cultural resistance, focusing on how artists’ lived experiences shape, and in turn, become shaped by their engagement with Palestine solidarity. Using an ethnographic approach, the study draws on online and offline participant observation and interviews with six artists. Applying Foucault’s six principles of heterotopia, the research reveals how artists’ experiences are defined by intersecting and contradictory elements, including tensions between authenticity, performativity, and neoliberal constraints, as well as the desire to use the underground for both political action and escape. A significant finding is the role of online platforms in enabling artists to inform Western audiences, highlighting cyberspace’s heterotopic qualities. For many, Palestinian liberation is a symbol of anti-colonial resistance embedded in cultural identity, shaping the underground scene as a heterotopia where resistance and reimagining of normative structures occur across physical, metaphorical, and virtual spaces.
Keywords: Culture; Resistance; Transnational Solidarity; Heterotopia; Palestine; Egypt; Decolonization